South African Renal Registry Annual Report 2017 - Davids, M Razeen; Jardine, Thabiet; Marais, Nicola; Zunza, Moleen; Jacobs, Julian C; Sebastian, Sajith (African Journal of Nephrology, 2019)
The sixth annual report of the South African Renal Registry summarises the 2017 data on renal replacement therapy (RRT) for patients with end-stage renal disease (ESRD) in South Africa. In December 2017, the number of patients with ESRD who were treated with chronic dialysis or transplantation stood at 10 744, a prevalence of 190 per million population (pmp). The growing prevalence observed since the registry was established is due mainly to the increasing numbers of patients accessing haemodialysis in the private sector, where the prevalence was 855 pmp. In the public sector, which serves 84% of the South African population, the prevalence of RRT (66 pmp) remained below the level reported for 1994, so that the disparity in access continued to increase. The disparities between provinces remained, with Limpopo and Mpumalanga the most under-served, as did the disparities between ethnic groups, with Blacks being the most under-served group. The Western Cape was the province with the highest public sector treatment rates and was also where most of the country’s public sector kidney transplants were performed.